2019
DOI: 10.4018/978-1-5225-5724-1.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Diversity, Inclusion, and Belongingness at an HBCU

Abstract: Most studies about inclusion of traditional minority groups and women on university campuses have been conducted at Predominantly White Institutions with student populations. This chapter focuses on the experiences, perceptions, and implications of diversity, belongingness, and inclusion of faculty at Historically Black Colleges and Universities (HBCUs). Data collected from students, staff, and faculty highlight the diversity and positive climate at HBCUs but indicate that there are important differences in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
0
1
Order By: Relevance
“…Chapter 11 also examines inclusion and belongingness of faculty, but from the perspective of faculty at Historic Black Colleges and Universities (HBCUs) and notes that research on campus climate, diversity, and inclusion has focused mainly on Predominantly White Institutions (PWI). Results from this study reported no racial tensions between Black and non-Black students, without significant differences in perception of belongingness and inclusion at HBCUs (hiAtt et al, 2019). However, the experience of faculty members shows a slightly different picture, which challenges previous studies on campus climate (ngwAinmBi, 2006;rAnkin & reAson, 2005).…”
contrasting
confidence: 84%
“…Chapter 11 also examines inclusion and belongingness of faculty, but from the perspective of faculty at Historic Black Colleges and Universities (HBCUs) and notes that research on campus climate, diversity, and inclusion has focused mainly on Predominantly White Institutions (PWI). Results from this study reported no racial tensions between Black and non-Black students, without significant differences in perception of belongingness and inclusion at HBCUs (hiAtt et al, 2019). However, the experience of faculty members shows a slightly different picture, which challenges previous studies on campus climate (ngwAinmBi, 2006;rAnkin & reAson, 2005).…”
contrasting
confidence: 84%